A fast-responsive mitochondria-targeted fluorescent probe detecting endogenous hypochlorite in living RAW 264.7 cells and nude mouse. Issue 8 (9th December 2014) - Xiao, Hongde; Xin, Kai; Dou, Haifang; Yin, Gui; Quan, Yiwu; Wang, Ruiyong
Abstract : A very fast-responsive fluorescent probe for imaging mitochondrial ClO − was prepared. The probe was successfully applied in the imaging of endogenous ClO − in the mitochondria of RAW 264.7 cells and living nude mouse. Abstract : A very fast-responsive fluorescent probe PZ–Py for imaging mitochondrial HClO/ClO −, with a relatively long emission wavelength, was prepared. The limit of detection was evaluated to be 17.9 nM. Moreover, the probe PZ–Py was successfully applied in the imaging of endogenous HClO/ClO − in the mitochondria of RAW 264.7 cells and living nude mouse.